The Role of Clean Energy and Clean Transportation in Mitigating Climate Change: A Case Study of BTS Skytrain in Bangkok, Thailand - Trirat, Cara Sasa; Siriwato, Sasiphattra (Journal of Contemporary Social Sciences and Humanities, 2025)
This research paper examines the vital role of clean energy in mitigating climate change, with a focus on the BTS Skytrain system in Bangkok, Thailand. By analyzing this prominent clean transportation infrastructure, the study aims to identify both challenges and opportunities for integrating renewable energy sources into public transit networks. The objectives are to assess how the Bangkok Mass Transit System (BTS) contributes to climate change mitigation and to evaluate the effects of clean energy and transportation policies in the city. The researcher conducted interviews with six participants: three BTS personnel and three government officials specializing in energy, climate, and transportation. Findings reveal that the BTS is Thailand’s first carbon-neutral rail service, significantly reducing greenhouse gas emissions through electric-powered operations. The BTS supports the government sustainability goals and promotes clean mobility, playing a crucial role in Thailand’s transition to carbon neutrality by 2050. Moreover, the study highlights that clean energy and transportation policies in Bangkok are essential for combating climate change by reducing emissions and enhancing energy efficiency. These policies facilitate the adoption of renewable energy and electric vehicles, improving air quality and public health. Ultimately, Thailand’s initiatives align with global efforts, demonstrating significant progress toward achieving carbon neutrality and fostering sustainable urban development.